Analisis Praktik Microteaching Mahasiswa Calon Guru Matematika dalam Perspektif Pembelajaran Inklusif - Dian Nataria Oktaviani; Rizqi Amaliyakh Sholikhakh; Herani Tri Lestiana (J-PiMat : Jurnal Pendidikan Matematika, 2026)
Microteaching practices have not yet been fully utilized as a reflective platform for developing inclusive teaching competencies among prospective mathematics teachers. However, microteaching is important for obtaining a factual overview of the readiness of prospective mathematics teachers to accommodate diverse student learning needs through accessible, adaptive, and participatory instruction. This study employed a descriptive approach with both quantitative and qualitative analyses, involving 22 fifth-semester students of the Mathematics Education program. The descriptive approach was chosen to obtain an empirical portrayal of microteaching practices, analyzed from the perspective of inclusive education. The instrument used was a validated observation sheet. Quantitative analysis was applied to describe trends in observation scores, while qualitative analysis was used to strengthen data interpretation through observational notes. The results indicate that the microteaching practices of prospective mathematics teachers demonstrate fairly good basic teaching skills and begin to reflect several principles of inclusive learning. However, further reinforcement is needed, particularly in the areas of differentiated instructional strategies, responsiveness to diverse student needs, and the implementation of formative assessment and adaptive feedback. Therefore, microteaching practices need to be more systematically integrated with the principles of inclusive learning.Keyword: Microteaching; Inclusive education; Prospective mathematics teachers.